2009
DOI: 10.1038/npp.2009.155
|View full text |Cite
|
Sign up to set email alerts
|

Reversal-Specific Learning Impairments After a Binge Regimen of Methamphetamine in Rats: Possible Involvement of Striatal Dopamine

Abstract: A growing body of evidence indicates that protracted use of methamphetamine (mAMPH) causes long-term impairments in cognitive function in humans. Aside from the widely-reported problems with attention, mAMPH users exhibit learning and memory deficits, particularly on tasks requiring response control. Although binge mAMPH administration to animals results in cognitive deficits, few studies have attempted to test behavioral flexibility in animals following mAMPH exposure. The aim of the current study was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
102
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 72 publications
(90 reference statements)
17
102
1
Order By: Relevance
“…DAT heterozygotes and GBR 12909-treated mice were able to learn, but learning was significantly slower (more trials to criterion) than in WT and control mice and they committed more commission errors to the criterion in the Rev stage (and IDS) than WT and control mice. Difficulties in the reversal task have been previously shown in DAT+/− mice when tested in the H-maze (Del'Guidice et al 2014) and have also been produced by reductions in striatal dopamine transporters evoked by methamphetamine administration (Izquierdo et al 2010). Treatment of mice with the potent and selective DAT inhibitor GBR 12909 (van der Zee et al 1980, Heikkila and Manzino 1984, Andersen 1989) would be expected initially to reduce DAT activity, but subsequently upon drug withdrawal, induce a rebound DAT over-expression, as has been previously postulated (Hewitt et al 2005(Hewitt et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…DAT heterozygotes and GBR 12909-treated mice were able to learn, but learning was significantly slower (more trials to criterion) than in WT and control mice and they committed more commission errors to the criterion in the Rev stage (and IDS) than WT and control mice. Difficulties in the reversal task have been previously shown in DAT+/− mice when tested in the H-maze (Del'Guidice et al 2014) and have also been produced by reductions in striatal dopamine transporters evoked by methamphetamine administration (Izquierdo et al 2010). Treatment of mice with the potent and selective DAT inhibitor GBR 12909 (van der Zee et al 1980, Heikkila and Manzino 1984, Andersen 1989) would be expected initially to reduce DAT activity, but subsequently upon drug withdrawal, induce a rebound DAT over-expression, as has been previously postulated (Hewitt et al 2005(Hewitt et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on rodent models of Meth addiction have recently focused on drug bingeing paradigms to investigate Meth-induced behavioral impairments (Belcher et al, 2008;Izquierdo et al, 2010;O'Dell et al, 2011), neuroplastic changes (Brennan et al, 2010), and neurotoxicity (Moszczynska et al, 1998;Kuczenski et al, 2007;Graham et al, 2008). The main objective of these studies was to achieve plasma drug levels in the rat close to those found in human Meth addicts.…”
Section: Discussionmentioning
confidence: 99%
“…When assessed at least 1 week after MA administration, rats and mice that are administered large, binge doses of MA (X4 mg/kg per dose, often multiple times per day) exhibit deficits in several cognitive domains, including object recognition memory (Belcher et al, 2005;Siegel et al, 2010), odor recognition memory (O'Dell et al, 2011), spatial learning (Acevedo et al, 2007;Vorhees et al, 2009), sequential learning (Chapman et al, 2001;Daberkow et al, 2005), path integration learning (Herring et al, 2008), working memory (Mizoguchi et al, 2011), effort discounting (similar to delay discounting) (Kosheleff et al, 2012), and reversal learning (Izquierdo et al, 2010).…”
Section: Animals Exposed To Ma Will Show Cognitive Decline Particulamentioning
confidence: 99%